If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6.4=v/4
We move all terms to the left:
-6.4-(v/4)=0
We add all the numbers together, and all the variables
-(+v/4)-6.4=0
We get rid of parentheses
-v/4-6.4=0
We multiply all the terms by the denominator
-v-(6.4)*4=0
We add all the numbers together, and all the variables
-1v-25.6=0
We move all terms containing v to the left, all other terms to the right
-v=25.6
v=25.6/-1
v=-25+0.6/1
| -m=-9+8m | | 3x*3-27x=0 | | 3(-5+4)+5x+-1=-39 | | 9=4k−3 | | t-32=96. | | -10c+3=-8c+5 | | 7(2-5x=154 | | 13=v/4 | | 2+2z=18 | | 4= 12(3x+4) | | G(x)=20-3x | | 11-2u=5 | | -9.7=-3.3=v/4 | | 4g+5(7g-3)=(g-5) | | 12x-5=672 | | 90=1.5x^2+8/ | | 5(3z-3)=40 | | 5= 27(10x+35) | | 5= 27(10x+35)72 (10x+35 | | X+4y=600 | | 3x³+5x²-2x=0 | | 0.5(4x+14)=(X-7) | | 2(2x-7)=x+10 | | 6x+2x+6=5x-15 | | 1/2d−12=24d= | | 1/2d−12=24d | | 3/4x+1/2x= | | 8=4x=-4 | | 154=-8x+7 | | 2b+23=85 | | 2+3(x-5)=2x=5 | | 6x+27=14÷-35 |